Enhanced External Counterpulsation Is Cost‐Effective in Reducing Hospital Costs in Refractory Angina Patients - Lawson, William E. (Clin Cardiol, 2015)
BACKGROUND: Enhanced external counterpulsation (EECP) is effective in the treatment of refractory angina, a condition suffered by 1.7 million Americans. Declining cardiovascular mortality and appropriate use criteria may further increase this number. HYPOTHESIS: EECP is hypothesized to be cost‐effective in reducing hospitalizations in refractory angina patients. METHODS: The data used in this analysis were collected in phase II of the International EECP Patient Registry (IEPR‐II). Data were collected on changes in Canadian Cardiovascular Society functional class, Duke Activity Status Index, and number of hospitalizations in the 6 months prior to EECP and in the 6‐ and 12‐month intervals following EECP. Estimates of the changes in annual cost of all‐cause hospitalization before and after EECP therapy were calculated by the product of the differences in hospitalization rates in the 6‐month interval before and after EECP treatment and estimated hospitalization and physician charges after subtracting the average cost of EECP. RESULTS: Data for 1015 patients were analyzed. Hospitalization occurred in 55.2% of patients, an average of 1.7 ± 1.4 hospitalizations/patient, in the 6‐month period before 35 hours of EECP; and in 24.4%, an average of 1.4 ± 1.0 hospitalizations/patient, during the 6‐ to 12‐month period after EECP. The average hospitalization and physician charge in the US was $17 995, and the average EECP cost was $4880, yielding an annual cost savings/patient of $17 074. CONCLUSIONS: Treatment of refractory angina patients with EECP resulted in improvement in angina and functional class accompanied by a sustained reduction in health care costs over 1 year of follow‐up.